The YY1/MMP2 axis promotes trophoblast invasion at the maternal–fetal interface - Tian, Fu‐Ju (J Pathol, 2016)
YY1 is a sequence‐specific DNA‐binding transcription factor that has many important biological roles. However, its function in trophoblasts at the maternal–fetal interface remains to be elucidated. In this study, we used an mRNA microarray and reverse transcription qPCR and compared the YY1 mRNA expression level in trophoblasts between patients with recurrent miscarriage (RM) and healthy control subjects. Our results revealed that YY1 mRNA expression was significantly lower in the trophoblasts of the RM group compared with the healthy control group. Furthermore, immunofluorescence and immunohistochemical data showed that YY1 was highly expressed in human placental villi during early pregnancy, especially in cytotrophoblast cells and invasive extravillous trophoblasts, and it was expressed at a much lower level in the placental villi of term pregnancy. YY1 overexpression enhanced, and knockdown repressed, the invasion and proliferation of trophoblasts. Antibody array screening revealed that YY1 significantly promoted MMP2 expression in trophoblasts. Bioinformatics analysis identified three YY1‐binding sites in the MMP2 promoter region, and chromatin immunoprecipitation analysis verified that YY1 binds directly to its promoter region. Importantly, inhibition of YY1 by siRNA clearly decreased trophoblast invasion in an ex vivo explant culture model. Overall, our findings revealed a new regulatory pathway of YY1/MMP2 in trophoblast cell invasion during early pregnancy and indicated that YY1 may be involved in the pathogenesis of RM. © 2016 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.